Goal Pursuit and their Relationship with Fear of Negative Evaluation of the Students Department of Psychological Counseling and Educational Guidance (Journal of the College of Basic Education, 2026)
This study aimed to identify the level of goal pursuit among students of the Department of Psychological Counseling and Educational Guidance, and to examine the differences in goal pursuit based on the gender variable (male – female). It also aimed to explore the level of fear of negative evaluation among these students and to identify gender based differences in this fear (male – female). Additionally, the study sought to determine the correlation between goal pursuit and fear of negative evaluation.To measure goal pursuit, the researcher used the Brandtstädter & Renner (1990) scale, while Leary’s (1983) scale was used to measure fear of negative evaluation. The research sample consisted of 200 male and female students.The results revealed that the participants demonstrated a high level of goal pursuit, as well as a high level of fear of negative evaluation. Notably, the study found a positive correlation between goal pursuit and fear of negative evaluation.